Assignment of a Claim Under an Obligation in Which the Identity of the Obligee Is Essential for the Obligor - A. A. Martsun (Сибирское юридическое обозрение, 2020)
The Plenum of the Supreme Court of the Russian Federation adopted a resolution of December 21, 2017 No. 54 “On some issues of application of the provisions of Chapter 24 of the Civil Code of the Russian Federation on the change of persons in an obligation on the basis of a transaction", which sets out important clarifications regarding the application standards contained in this chapter. At the same time, not all issues related to the assignment of the claim were resolved by the above resolution. One of these issues is the definition of the term “essential value of the identity of the creditor” or approximate criteria for such a value in the context of the need to obtain the latter’s consent to the assignment of rights. The presence of this problem is rightly indicated in the scientific literature [3, p. 549–655, 688–713]. The Author examines the Model Rules of European Private Law and the UNIDROIT principles in order to find a solution to the problem. Attention is drawn to the problem of determining the essential value of the creditor for the debtor in the case of assignment of the right of claim, as well as to the consequences of making the assignment without the consent of the debtor under an obligation in which the identity of the creditor was essential.In the Author's opinion, the identity of the creditor is recognized as essential for the debtor when the connection between the debtor and the creditor arose as a result of the conclusion of a transaction that has a personallyconfidential nature, or if the connection arose during the conclusion of other transactions in the case when the connection was broken during the execution assignment of rights entails or may entail a significant deprivation for the debtor of what he had the right to count on when concluding a transaction with the creditor.In addition, situations are considered that are an exception to the presumption of the absence of a significant value of the creditor's personality for the assignment of claims for monetary obligations. The author also points out that the consequence of the transaction on the assignment of rights without the consent of the debtor in the context of paragraph 2 of Art. 388 of the Civil Code of the Russian Federation is the nullity of the transaction on the basis of paragraph 2 of Art. 168 of the Civil Code of the Russian Federation.